2018
DOI: 10.1186/s41065-018-0066-4
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Drosophila ATR homologous checkpoint kinase Mei-41 induces a G2/M checkpoint in Drosophila imaginal tissue

Abstract: BackgroundDNA damage generally results in the activation of ATM/ATR kinases and the downstream checkpoint kinases Chk1/Chk2. In Drosophila melanogaster, the ATR homologue meiotic 41 (mei-41) is pivotal to DNA damage repair and cell cycle checkpoint signalling. Although various mei-41 mutant alleles have been analyzed in the past, no gain-of-function allele is yet available. To fill this gap, we have generated transgenic flies allowing temporal and tissue-specific induction of mei-41.ResultsOverexpression of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Taken together, our findings suggest that Wnt signaling drives high levels of Chk1 expression in tracheoblasts and that high levels of Chk1 in cells that have a basal level of ATR activity is sufficient to induce G2 arrest. Consistent with the proposed model, studies in yeast (Ford et al, 1994), Drosophila (Bayer et al, 2018) and Xenopus (Kumagai et al, 1998) have shown that the overexpression of Chk1 is sufficient to arrest cells in G2.…”
Section: Discussionsupporting
confidence: 68%
“…Taken together, our findings suggest that Wnt signaling drives high levels of Chk1 expression in tracheoblasts and that high levels of Chk1 in cells that have a basal level of ATR activity is sufficient to induce G2 arrest. Consistent with the proposed model, studies in yeast (Ford et al, 1994), Drosophila (Bayer et al, 2018) and Xenopus (Kumagai et al, 1998) have shown that the overexpression of Chk1 is sufficient to arrest cells in G2.…”
Section: Discussionsupporting
confidence: 68%
“…In light of the findings that ROS depletion does not perturb Chk1 expression but does perturb Chk1 phosphorylation and function, we hypothesized that ROS may regulate Chk1 phosphorylation in some manner. The ATR-dependent phosphorylation of Chk1 at serine 373 is thought to be necessary for its activation ( Liu et al, 2000 ; Patil et al, 2013 ; Bayer et al, 2018 ). Our immunohistochemical analyses are consistent with these findings.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, both pChk1 and Chk1 mRNA levels are high in L2 and early L3 and diminish at 32–40 h L3. Studies in yeast ( Ford et al, 1994 ), Drosophila ( Bayer et al, 2018 ) and Xenopus ( Kumagai et al, 1998 ) have shown that the overexpression of Chk1 is sufficient to induce G2 arrest. Thus, we hypothesized that Wnt signaling facilitates high levels of pChk1 via induction of high levels of Chk1 expression.…”
Section: Resultsmentioning
confidence: 99%